MODEL PENINGKATAN KINERJA GURU MELALUI KNOWLEDGE SHARING DAN KOMPETENSI YANG DIMEDIASI KREATIVITAS (Studi pada Guru SMKN Wonosari, Kabupaten Malang) - Budiono, Budiono; Muryati, Muryati; Nasharuddin Mas (Juremi: Jurnal Riset Ekonomi, 2024)
The aim of this research is to obtain empirical evidence regarding knowledge sharing abilities and competencies on teacher performance, both directly and through the mediation of creativity. This type of research is quantitative with the SEM-SmartPLS method. Data was obtained through questionnaires distributed by census to 38 Wonosari Vocational School teachers, Malang Regency. Empirical evidence shows that knowledge sharing is able to encourage increased teacher performance, both directly and through the mediation of creativity. Meanwhile, competency is not able to encourage increased teacher performance, either directly or through the mediation of creativity. However, creativity still has an influence on the performance of teachers at Wonosari Vocational School, Malang Regency